The Role of Social Capital in African Americans’ Attempts to Reduce and Quit Cocaine Use - Cheney, Ann M. (Subst Use Misuse, 2016)
BACKGROUND: Research examining substance users’ recovery has focused on individual-level outcomes while paying limited attention to the contexts within which individuals are embedded, and the social processes involved in recovery. OBJECTIVES: This paper examines factors underlying African American cocaine users’ decisions to reduce or quit cocaine use and uses practice theory to understand how lifestyle changes and shifts in social networks facilitate access to the capital needed to change cocaine use patterns. METHODS: The study, an in-depth analysis of substance-use life history interviews carried out from 2010 to 2012, included 51 currently not-in-treatment African American cocaine users in the Arkansas Mississippi Delta region. A blended inductive and deductive approach to data analysis was used to examine the socio-cultural and economic processes shaping cocaine use and recovery. RESULTS: The majority of participants reported at least one lifetime attempt to reduce or quit cocaine use; motivations to reduce use or quit included desires to meet social role expectations, being tired of using, and incarceration. Abstinence-supporting networks, participation in conventional activities, and religious and spiritual practices afforded access to capital, facilitating cocaine use reduction and sobriety. CONCLUSIONS: Interventions designed to increase connection to and support from non-drug using family and friends with access to recovery capital (e.g., employment, faith community, and education) might be ideal methods to reduce substance use among minorities in low-income, resource-poor communities.